Estimacão da qualidade industrial da batata (Solanum tuberosum L.) atraves do uso da isoenzima glutamato oxaloacetato transaminase - M.A. Andreu; A. da S. Pereira (RIA: Revista Investigaciones Agropecuarias)
High dry matter content and the color of the final processed product are among the most important characteristics for the potato processing industry. The use of isoenzymes for a rapid prediction of these characteristics in tetraploid potatoes resulting in an increased selection efficiency by reducing the time required to get good results, was not completely explored yet. The objective of this study was to determine the association between the isoenzyme glutamate oxaloacetate transaminase and the dry matter contents and color of the potato tubers chips in different genotypes of ten commercial varieties and ten clonal families of potato (Solanum tuberosum L.) eletrophoretically evaluated. To determine the association, 2x2 Chi-square contingency tables were used with correction for continuity. Results of the comparisons indicated a significant association between the 1.00 band of the evaluated enzyme and the chips color, which allowed an early estimation by this enzyme of the effect of frying. Did not have association between the dry matter and the band 1,00, contradicting other researches with diploid wild potatoes.